Morphology and Morphometrical studies on Semi lunar Heart valves of Indigenous Cattle (Bos indicus) - Akhtar, S; Hossain, FMA; Siddiqui, MSI; Alam, M; Islam, MN (International Journal of Natural Sciences, 2011)
Twenty heart specimens of healthy indigenous cattle (Bos indicus) of different age group (04 groups) in Sylhet District were collected for gross morphology and morphometrical analysis of cusps or leaflets and papillary muscles to study the measurement of the length of the free margin of the cusps of the aortic and pulmonary valves and anatomical assessment for future bioprosthetic purpose for heterografting in the cardiac valvular human patients. It was found that the pulmonary valves consisted of three semilunar valve leaflets, the wall of the sinuses, the interleaflet triangles, the commissures and the sinotubular junction; whereas the aortic heart valve leaflets of indigenous cattle were three in number: right, left and noncoronary. Each leaflet of the valve has a central lamina fibrosa at their free margin of which the thickened part in the midpoint of the lunula formed the corpus arantii. The length of the right and posterior pulmonary cusp in this study was statistically significant (p<.005) but the length of the left pulmonary cusp was not significant in all age groups of animal. The mean length of the right coronary cusps (RCC), left coronary cusps (LCC) and non coronary cusps (NCC) was statistically not significant irrespective of their age groups of animal studied. This valve might be used for manufacturing tissue valve for Bioprosthesis. Keywords: Indigenous cattle; heart valve; morphology; morphometry. DOI: http://dx.doi.org/10.3329/ijns.v1i1.8608 International Journal of Natural Sciences (2011), 1(1):7-11